Rethinking Multicultural EFL Instruction in Indonesian Junior High Schools: Teachers’ Challenges and Classroom Realities - Mohammad Sata, Mohammad Rafii; Abduh, Amirullah; Baa, Sultan; Wahyuddin (LETS: Journal of Linguistics and English Teaching Studies, 2026)
Multicultural instruction has become increasingly important in English as a Foreign Language (EFL) classrooms as students bring diverse cultural, linguistic, and social backgrounds into the learning process. However, its classroom implementation remains challenging, particularly in junior high school contexts where teachers must balance language objectives, student diversity, curriculum demands, and limited institutional support. This study employed a qualitative case study design to investigate teachers’ challenges in implementing multicultural instruction in Indonesian junior high school EFL classrooms. Data were collected through classroom observation, semi-structured interviews, and document analysis involving English teachers, school principals, and MGMP Head. The data were analysed thematically to identify recurring patterns related to teachers’ challenges. The findings reveal three major challenges: limited institutional support, teachers faced a lack of multicultural teaching materials, and Student diversity in Classroom Interaction. The study concludes that multicultural instruction in Indonesian EFL classrooms operates as an adaptive and contextualized pedagogical practice that requires stronger institutional support, culturally relevant resources, and sustained teacher professional development in interacting students’ diversity. The findings imply the need for stronger school support, localized multicultural materials, and continues teacher training to strengthen inclusive classroom practice. However, due to the limited number of participants and the specific junior high school context, further research involving broader settings and larger participant group is needed to provide more comprehensive insight into multicultural instruction.